DEMOCRACY, EDUCATION, AND GENDER INEQUALITY: EVIDENCE FROM PROVINCIAL PANEL DATA DYNAMICS - Irfan; Maryana; Rinaldi Syahputra (CV. Radja Publika, 2026)
This study aims to analyze the dynamics of inclusive development at the provincial/district level in Indonesia by emphasizing the differences in the short-term and long-term influences of its determinants. This study uses panel data and applies the Panel Autoregressive Distributed Lag (Panel ARDL) method. This method was chosen because it is able to accommodate differences in regional characteristics and varying degrees of variable integration. The estimation results show a stable long-term relationship between the democracy index in Indonesia and the explanatory variables, as indicated by the negative and significant error correction term coefficient . In the short term, gender inequality has a negative and significant effect on the democracy index, while economic participation has a positive and significant effect. The long-term results confirm that gender inequality is a structural obstacle to the democracy index, while economic participation is a key driver of increasing sustainable inclusive development at the regional level. Other social variables show relatively weaker effects, both in the short and long term. The findings of this study emphasize the importance of regional development policies oriented towards reducing gender inequality and strengthening economic participation as key strategies for boosting democracy in Indonesia. Methodologically, this study contributes to the literature by applying the ARDL Panel approach to the Indonesian subnational context, thus providing a more comprehensive understanding of the dynamics of inclusive development across regions.